Propuesta de un producto turístico para el pueblo mágico de la parroquia de Saraguro del cantón Saraguro - Amoroso Castillo, Michelle Katherine (2023)
Tourism is a potential source for the development of the parish of Saraguro in the Canton Saraguro, as it has natural and cultural attractions that are the fundamental basis for promoting tourism in the area. The present research aims to design a tourist product, taking into account that the town of Saraguro was declared in 2020 as a "Magical Town" of Ecuador, allowing the development of a tourist route, a product identified in the Saraguro Tourism Development Plan. For the design of this product, a tourist diagnosis was previously carried out in the study area, where twelve tourist attractions were identified, which were determined through the MINTURN cards, as well as adapted ICCA matrices were used, which helped to determine the actors involved in the route and the improvements of the areas involved, which are: the urban center of Saraguro and the communities of Gunudel, Ñamarín, and Tuncarta. For the feasibility and demand study, a market analysis was carried out, which allowed us to identify the tourist profile. In this way, doing a previous study of supply and demand allows the development of a tourist route with three derived circuits, detailing its route, tourist attractions, and itinerary. Based on the diffusion and promotion, it is proposed to carry out post-advertising through the social networks of the Saraguro Parish GAD, in local tourist operators, and on official pages of the identified tourist attractions and services. The development of the Tourist Route in the magical town of Saraguro will help to make the culture, history, and ethnography known in a single tourist product